Nonlinear control for battery energy storage systems in power grids (2018)
This paper presents a nonlinear control strategy to integrate Battery Energy Storage Systems (BESS) in electrical power systems connected through Voltage Source Converters (VSCs). Exact feedback linearization control technique based on the dynamical model of the system is employed as control strategy. Two VSCs topologies are proposed to control the generated/consumed current by the BESS. The proposed controller allows the charge/discharge of the BESS with either constant current or constant power. The VSC is employed to independently compensate for the active and reactive power from/to the grid to/from the BESS. A radial distribution network modeled in MATLAB/SIMULINK is implemented as a test system to validate the functionality of the controller under two scenarios. © 2018 IEEE.